Study of metabolite differences of flue‐cured tobacco from different regions using a pseudotargeted gas chromatography with mass spectrometry selected‐ion monitoring method. Issue 16 (24th June 2014) - Zhao, Yanni; Zhao, Chunxia; Li, Yanli; Chang, Yuwei; Zhang, Junjie; Zeng, Zhongda; Lu, Xin; Xu, Guowang
<x xml:space="preserve">Abstract</x> A pseudotargeted method based on gas chromatography and mass spectrometry with selected‐ion monitoring was established to investigate the metabolite differences of flue‐cured tobacco from three different growing regions. The mixed solvent of acetonitrile/isopropanol/water (3:3:2, v/v/v) was chosen as the optimal extraction system based on the good repeatability and extraction efficiency. A self‐developed software coupled with commercial software was used to establish the pseudotargeted method including 289 peaks and 47 groups. Multivariable statistical analysis indicated that tobacco samples can be obviously separated based on the geographical origins. On the basis of a Mann–Whitney U test, organic acids, phenols, and alkaloids had higher levels in Hunan province. In contrast, a large proportion of amino acids (including l‐tyrosine, l‐proline, and serine), sucrose, and linoleic acid were the highest in Yunnan province. Meanwhile, multiple metabolic pathways (including carbohydrate metabolism, tricarboxylic acid cycle, and nitrogen metabolism) were influenced by growing regions. Twenty‐eight differential metabolites, which had great contributions to the classification of tobacco samples of three growing regions, were further defined. The results demonstrated that the developed pseudotargeted method was a powerful tool to investigate the metabolic profiling of tobacco leaves and discriminate tobacco leaves of different growing regions.